2010
DOI: 10.1007/s00018-010-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

The epididymis-specific antimicrobial peptide β-defensin 15 is required for sperm motility and male fertility in the rat (Rattus norvegicus)

Abstract: Spermatozoa acquire forward motility and fertilizing capacity during their transit through the epididymis. The maturation process involves modifications of the sperm surface by different proteins that are secreted by a series of specialized regions in the epididymal epithelium. Here we show that the rat epididymis-specific β-defensin 15 (Defb15) exhibits an androgen-dependent expression pattern, and it can bind to the acrosomal region of caput sperm. Coculture of caput spermatozoa with Defb15 antibody in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 44 publications
(58 reference statements)
3
102
0
1
Order By: Relevance
“…Although it is still unclear why such a wide range of ␤-defensins are present in the male reproductive tract, their diverse functions can be briefly classified into three types: their common role in innate immunity by exhibiting antimicrobial activity in the reproductive system (28, 39) and non-reproductive systems (19); sperm maturation-related functions (28,40,41); and immunoregulating activity, which has been shown in nonreproductive systems (19). In addition to their expression in reproductive tissues, the majority of human ␤-defensins are also expressed in non-reproductive tissues (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is still unclear why such a wide range of ␤-defensins are present in the male reproductive tract, their diverse functions can be briefly classified into three types: their common role in innate immunity by exhibiting antimicrobial activity in the reproductive system (28, 39) and non-reproductive systems (19); sperm maturation-related functions (28,40,41); and immunoregulating activity, which has been shown in nonreproductive systems (19). In addition to their expression in reproductive tissues, the majority of human ␤-defensins are also expressed in non-reproductive tissues (19).…”
Section: Discussionmentioning
confidence: 99%
“…1d). The generation of the antibody followed the protocols described previously (28). The antibody could recognize Ͻ5 ng of antigen protein in Western blot assays.…”
Section: Expression Of Defb114 In the Human Epididymis-humanmentioning
confidence: 99%
“…Identification and characterization of differentially expressed genes in epididymis have provided us additional insight into the mechanisms of sperm maturation. Our previous study demonstrated that several epididymal proteins, such as Bin1b (5), HongrES1 (46), and Defb15 (44), are essential in sperm motility, capacitation, and male fertility, respectively. In the present study, we identified an epididymis-specific gene, Spink13, and demonstrated its physiological function in regulation of acrosome reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols used for examination of the knockdown efficiency and production of lentiviral particles were as previously described (44). Briefly, the psiRNA constructs and a pcDNA 3.0 vector expressing Spink13 were co-transfected into the mouse epididymal epithelial cells (PC1) using Lipofectamine 2000 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation